2005
DOI: 10.1111/j.1365-2125.2004.02334.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of glyceryl trinitrate and amyl nitrite on pulse wave reflection and augmentation index

Abstract: AimsThe influence of vasodilators on augmentation index (AIx) offers a simple, rapid and noninvasive method of evaluating vascular function. Glyceryl trinitrate (GTN) is widely used as an endothelium-independent vasodilator, although other nitrates that are shorter acting may have advantages in clinical studies. The aim of this study was to compare the effects of two short-acting nitrates, GTN and amyl nitrite, which have differing pharmacodynamic profiles. MethodsTwenty-one healthy volunteers (15 male; mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In a previous study in rats, we demonstrated that NO given immediately before a 45-min air dive effectively reduced bubble formation (18). Because of the fact that NO reduces venous tone through a reduction of the preload and hence reduces CO (6,8), part of the effect on bubble formation could have been caused by a reduction in gas uptake. This is less likely in the present study since we are close to saturation and since our NO donor was given at the end of the bottom phase of the dive.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In a previous study in rats, we demonstrated that NO given immediately before a 45-min air dive effectively reduced bubble formation (18). Because of the fact that NO reduces venous tone through a reduction of the preload and hence reduces CO (6,8), part of the effect on bubble formation could have been caused by a reduction in gas uptake. This is less likely in the present study since we are close to saturation and since our NO donor was given at the end of the bottom phase of the dive.…”
Section: Discussionmentioning
confidence: 79%
“…The lower arteriovenous O 2 difference in the NO-treated animals (12%) 30 min after the start of decompression indicates on one hand that the O 2 extraction per unit of blood has decreased because perfusion has increased, which is also supported by the increase in heart rates seen in the experimental group. On the other hand, other studies have shown a slight decrease in cardiac output (CO) after administration of the drug, without changing the blood pressure (6). However, the experimental group showed a higher heart rate immediately after nitrate infusion compared with the control group.…”
Section: Discussionmentioning
confidence: 91%
“…Nitroglycerine will reduce peripheral vascular resistance and reduce venous tone, leading to a slight reduction in cardiac output with little change in blood pressure (7). This may influence uptake of inert gas.…”
Section: Discussionmentioning
confidence: 98%
“…This PWF information has become a powerful tool to investigate the cardiovascular response in vivo in humans to disease states and drugs. It was notably shown more reliable in detecting arterial triptan and nitrate-induced vascular effects than the classically used brachial artery diastolic (DBP) and systolic blood pressure (SBP) [25][26][27][28]. High resolution ultrasound allows the real time measurement of changes in the brachial artery diameter (BAD) induced by vasoactive drugs, notably triptans and nitrates [25].…”
Section: Introductionmentioning
confidence: 99%